A method to predict early-ejected plastic part air-cooling behavior towards quality mold design and less molding cycle time. (April 2019) - Fu, Junyu; Ma, Yongsheng
Highlights: A method proposed to predict early-ejected plastic part air-cooling behavior. The method proposed integrates MoldflowTM and AnsysTM by feeding MoldflowTM simulation results as the intermediate state data set into AnsysTM for air-cooling effect simulation. Towards early ejection of plastic part to achieve less molding cycle time. A real industrial case is used to show the effectiveness of the proposed method. Abstract: It is a common industrial practice to eject injection-molded plastic parts early, at a high temperature, and allow the parts to cool down in the air. This practice shortens the cycle time and reduces production cost. However, current commercial injection molding simulation software tools can only consider the in-mold cooling process. The simulation of the air-cooling stage after ejection is not well supported in such tools even though the air-cooling shrinkage is significant when plastic parts are ejected at high temperatures. The authors propose a Moldflow™-Ansys™ integrated FEA method to simulate the air-cooling process so that the air-cooling shrinkage can be considered at the early design stage and the quality of the part can be ensured with less molding cycle time. A real industrial case study is provided to show the procedure and its validation. The proposed method integrates Moldflow™ and Ansys™ by feeding Moldflow™ simulation results as the intermediate state data set into Ansys™ for air-cooling effect simulation. With a real testing product part ejected at a high temperature, the proposed approach shows promising predictions of the 3D warpage displacement. In this way, the cost factor of molding cycle time can be considered at the mold design stage and a cost-effective design can be developed.